Total Plasma Exchange for Hypertriglyceridaemia Complicated by Acute Pancreatitis: A Case Report - Dawlat Sany; Wael Ahmed Yousry; Wael Refai; Walid Hassan; Rami Qattan; Yasser Elsahawi (European Medical Journal)
Introduction: Hypertriglyceridaemia (HTG) is common and often precipitates into acute pancreatitis. Early diagnosis of HTG pancreatitis (HTGP) is essential for appropriate management to avoid recurrence of pancreatitis. Plasmapheresis was suggested as treatment modality to decline triglyceride levels, especially in critical patients with multiorgan failure. Few randomised studies are recorded regarding the value of plasmapheresis over classical therapy. Objective: To evaluate the value of plasmapheresis in patients with HTGP with worrisome signs as fever, tachycardia, high inflammatory markers, and pancreatitis. Methods: Clinical course and laboratory markers status after total plasma exchange (TPE) for HTG that is not responding to initial, traditional therapy by insulin infusion was reported. Results: The authors’ patient had an initial triglyceride level of 30 mmol/L, with a worsening clinical condition and acute pancreatitis. After TPE, there was a significant decline in their triglyceride serum levels (53%) after the first session, leading to marvellous recovery. Conclusion: The authors suggest treatment with TPE for systemic inflammation and HTGP-induced multiorgan failure. However, further research is necessary.